Effect of football practices on certain blood values of athletes - Çinar, Vedat; CengIz, Şebnem; Pala, Ragip; Dündar, Aykut (My University, 2013)
In this study, it is aimed to determine the effect of 10 days match program of football players on RBC (Erythrocyte), WBC (Leucocyte), PLT (Trombosit), HGB (Hemoglobin) blood values. Research is performed on 18 healthy male footballer subjects. All subjects participated in match program for total of 7 days, 90 minutes on one day within the framework of a 10 days match program. Blood samples were taken from all subjects in resting position before starting to the match program and 2 hours after the end of the last match. RBC (Erythrocyte), WBC (Leucocyte), PLT (Trombosit), HGB (Hemoglobin) levels were specified in the blood samples received. At the end of the application, RBC (Erythrocyte) levels of the group was higher than the pretest values which were the 1st measurement (p<0.05). There is no statistically important difference in the WBC (Leucocyte) values of the footballers at the end of matches (p>0.05). Posttest measurements of HGB (Hemoglobin) levels were higher than the pretest measurements, and the difference in between was statistically significant (p<0.05). In a similar way, PLT (Trombosit) values obtained at the end of match program were higher than the pretest measurement values taken before beginning to the match program, and the difference in between is important (p<0.05). As a result of this study, it can be stated that match program of 10 days has caused significant alterations in complete blood values of RBC (Erythrocyte), PLT (Trombosit), and HGB (Hemoglobin) values of footballers.
Keywords: Blood; Erythrocyte; Footbaal; Hematoloji; Training